COVID-19 AND INSTAGRAM: AN ANALYSIS OF IBERO-AMERICAN PUBLICATIONS - Reno, Denis [UNESP]; Martinez-Rolan, Xabier; Pineiro-Otero, Teresa; Versuti, Andrea (Univ Complutense Madrid, Fac Ciencias Informacion, 2021)
Understanding the role of communication promoted by Ibero-American society during the Coronavirus pandemic is fundamental to the construction of knowledge about the disease. In this scenario, Instagram occupies a privileged place, as it carries a diversity of possible languages. In addition, Instagram's relevance in the social networking landscape is growing. This article presents, from a study developed through big data analysis procedures, a first result of several that make up an international investigation on the subject. At the stage of the project, the quantitative volume of publications, the average publication per user and the participation of the various languages used in this analysis group were verified. It is expected that further investigations can be developed from the results presented here, especially due to the urgency of knowing the role of communication in the pandemic scenario in which we live.
Keywords: Communication; Photography; Instagram; Big Data; COVID-19; coronavirus; pandemic